The Phenomenon of Conversion from Orthodoxy to the Armenian Faith in the Russian Empire in the 19th - early 20th Century - Vladimir S. Blokhin (RUDN Journal of Russian History, 2020)
The article analyzes why and how persons of the Orthodox confession converted to the Armenian faith in the nineteenth- and early twentieth-century Russian Empire. This phenomenon is linked to the practice of mixed marriages between persons belonging to the Orthodox and Armenian confessions. While the status of non-Orthodox Christian confessions in Russia during the synodal period has received a good amount of scholarly attention, not much research has been devoted to the conversion from Orthodoxy to the Armenian faith, and to the issue of marriages between persons belonging to these faiths. The present paper identifies the motives and circumstances of religious conversions and the peculiarities of mixed marriages. It does so on the basis of unpublished documents from the funds of the National Archive of the Republic of Armenia. Equally new is the authors suggestion to consider these phenomena as an integral component in the history of Russian-Armenian church relations in the period 1828-1917. Until 1905, the regulations of the Orthodox Church demanded that after the conduction of an interreligious marriage, both spouses continued to practice their respective faiths, and their children were baptized in Orthodoxy. This is reflected in the metric books of the Erivan Pokrovsky Orthodox Cathedral (1880-1885). The analysis of archival documents allows us to conclude that after 1905, most of the conversions from Orthodoxy to the Armenian faith were performed by women who intended to marry men of the Armenian confession. The reason for this phenomenon is that interreligious marriages and the baptism of children born from mixed couples was still in the competence of the Russian Orthodox Church. Only if both partners belonged to the Armenian faith, the wedding could take place in the Armenian Church, and their children were brought up in the Armenian faith. In addition to matrimonial reasons, the article underlines some other important motives behind conversions from Orthodoxy to the Armenian confession.